Visioni critiche Recensioni teatrali da «l'Unità-Toscana» (1975-1983) - FERRONE, SIRO (Studi e saggi, 2016)
Like a two-faced Janus, Siro Ferrone carried out both research on theatre and theatre criticism, combining academic research and stage experience. His reviewer activity, carried out without interruptions, is now for the first time transcribed and organically collected in a volume. The articles, which appeared on the pages of "l'Unità-Toscana", are today an important source for the analysis of significant shows staged in the main Tuscan theatres between 1975 and 1983. The result is the documentation of a period of fertile and avant-garde theatrical production, here retraced through the aware and illuminating testimonies of one of the main Italian historians of performing arts.